100m Hurdle race: Time Analysis of Olympic Level Women - Tsiokanos Αθανάσιος (Inquiries in Physical Education and Sport, 2011)
Time parameters of six female hurdlers, taking part in the final race of the 100 m hurdles in the Olympic Games of Athens 2004, were managed and analyzed using video techniques. The parameters of approach run time, run-in time, inter-mediate touchdown times after each barrier, and interval times for the hurdle units were analyzed. The descriptive statistics demonstrated that the maximum running velocity is developed between the 5th and 6th barrier (interval time 0.97 sec), while the conducted correlation analysis demonstrated that statistically significant correlation (r= .82 - .98) is revealed between the final performance and the inter-mediate touchdown times after the 6th to 10th barrier. The relative temporal parameters, examining the temporal distribution of the competitive efforts during the race, were used for safe comparisons between the final race of the Athens 2004 and the World Championship of Athens 1997 and the Olympic Games of Seoul 1988. The findings of the study provide significant information for the programming and modelling of technical training of the women hurdlers.